Ризоморфний лабіринт як гетеротопія в романі Ю. Винничука «Мальва Ланда» - Коваленко (Шевчук), Діана; Kovalenko (Shevchuk), Diana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті здійснено інтерпретацію образу львівської сміттярки як гетеротопії або «іншого місця» в романі Ю. Винничука «Мальва Ланда»; установлено, що визначальними рисами гетеротопії, які увібрав у себе образ сміттярки, є можливість зосереджувати в собі множинність просторів, перебуваючи водночас в іншому просторі, й акумулювати час; визначено, що часопросторовий вимір роману конструюється за загальними зако¬нами постмодерного тексту та має форму ризоморфного лабіринту, у межах якого відбуваються радикальні екзистенційні трансформації. The article has interpretation of the image of Lviv's trash as heterotopia or «other place» in the Y. Vynnychuk’s novel «Malva Landa»; it is found, that defining features of heterotopia, which were included in the image of trash, is the ability to contain a plurality of spaces, while being in another space and accumulation of time; it is determined, that the timespace of text is defined by combination of two time and spatial planes: external (real) and internal (unreal). Real space is clearly defined geographically, but fantastic one is deployed on the territory of Lviv Trash, which appears in the novel as a kind of microcosm, a world apart with its own laws of existence. Time in the novel condenses, slows down and, intertwining with the space in a single continuum, is built on the laws of postmodern text, acquiring the form of rizoma-maze with endlessly divided space of meanings. Text timespace is constructed as a model of irreversible existential transformations, related to the passage of the way of life through the difficulties and the illusions of this world to the center and enlightenment.
Rizoma-maze as in the Y. Vynnychuk Novel «Malva Landa»
Keywords: гетеротопія; час; простір; ризоморфний лабіринт; ірреальний простір; heterotopia; time; space; rizoma-maze; surreal space